2018
DOI: 10.5897/jhf2017.0500
|View full text |Cite
|
Sign up to set email alerts
|

Collection and characterization of garlic (Allium sativm L.) germplasm for growth and bulb yield at Debre Markos, Ethiopia

Abstract: Garlic (Allium sativm L.) is the most widely used crop among cultivated Allium species in Ethiopia andit has a wide range of climatic and soil adaptation. Production of the crop is confronted with a number of problems and the total production and productivity in the country is low. Among many contributing factors, lack of improved varieties and garlic rust are the major ones. In view of this, an experiment was carried out to screening garlic germplasm for yield and diseases tolerance at Debre Markos University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 11 publications
2
25
0
Order By: Relevance
“…The largeness and heaviness of BW could be accounted to the number of cloves and clove weight. The present finding is in accordance with the results of Islam et al (2007) and Yeshiwas et al (2018) who reported significant variation for bulb weight due to genotypic difference. Additionally, in India, Rakesh Sharma et al (2018) found that bulb diameter and weight contributed maximum towards the total variability in their evaluated germplasm.…”
Section: Discussionsupporting
confidence: 94%
“…The largeness and heaviness of BW could be accounted to the number of cloves and clove weight. The present finding is in accordance with the results of Islam et al (2007) and Yeshiwas et al (2018) who reported significant variation for bulb weight due to genotypic difference. Additionally, in India, Rakesh Sharma et al (2018) found that bulb diameter and weight contributed maximum towards the total variability in their evaluated germplasm.…”
Section: Discussionsupporting
confidence: 94%
“…As a result of the interaction, a higher mean mass of bulb was noted in the cultivation of plants of cultivar 'Ornak' in all the variants of cultivation, relative to the remaining experimental treatments. An earlier study by Yeshiwas et al (2018) showed a considerably lower garlic bulb mass, varying from 4.87 to 17.51 g, and in a study by Albuquerque et al (2017) -from 7.57 to 14.47 g.…”
Section: Resultsmentioning
confidence: 74%
“…An earlier study by Petropoulsos et al (2018) showed that the number of cloves in a garlic bulb, depending on the cultivar, was from 4 to 6 pcs×plant -1 . On the other hand, Yeshiwas et al (2018) obtained somewhat higher results -from 10 to 20 pcs×plant -1 , while Albuquerque No significant effect of the factors and their interactions on the content of sugars in garlic was demonstrated. The analysed cultivars had an average content of 14.05 g 100 g -1 FM (fresh matter) total sugars and 1.0 g 100 g -1 FM reducing sugars.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Vegetables (including garlic) play an important role in rural modernization [1] and in providing additional income, as well as nutrition [2,3] when vegetables are cultivated as vegetable home garden. Garlic (Allium sativum) is one of Ethiopia's most important bulb crops and a popular spice [4]. It is the second most widely cultivated crop in the Alliaceae family.…”
Section: Introductionmentioning
confidence: 99%